Heterogeneity of Agents in Cellular Evacuation Model Explains the Decreasing Bottleneck Flow - Hrabák, Pavel; Šutý, Matej; Hotlib, Mykola (Collective Dynamics, 2024)
Heterogeneous crowd consisting of pedestrians with essentially diverse abilities behaves in certain aspects differently than a homogeneous crowd consisting of "average" pedestrians. This study investigates the influence of heterogeneity in aspects connected to the ability to navigate through a crowd in front of a bottleneck. Simulations of cellular multi-agent model suggest that the heterogeneity in ability to push through the crowd (represented by aggressiveness) and willingness to bypass the crowd (represented by sensitivity to occupation) may be responsible for the bottleneck flow decreasing in time – a phenomenon observed in experiments.